mRNA isolation from Citrus sinensis and cDNA synthesis for genes involved in flavonoids biosynthetic pathway - Nurul Nadiah Mohd Shuisma, 1994- 611592; Nur Izzati Mohd. Noh, 1987- 554028; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2017